Ulica Zielona - Nowaliński, Karol (1935- ). (Gdańsk, 1987)
Przedstawia kamienice nr 15-17 przy ulicy Zielonej w Gdańsku, 1987 r.
Tytuł ołówkiem na rewersie.
Keywords: Fotografie -- Polska -- Gdańsk; Ulice -- Polska -- Gdańsk -- 1945- -- fotografie; Gdańsk (Polska) -- 1970-2000 -- fotografie; Dolne Miasto (Gdańsk, Polska ; dzielnica) -- fotografie